PENGARUH PENERAPAN MODEL PEMBELAJARAN CONCEPTUAL UNDERSTANDING PROCEDURES TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XI MIPA SMAN1 LEMBAH GUMANTI - Mila Nurul Husna (Jurnal Edukasi dan Penelitian Matematika, 2022)
Mathematics learning result are basically the main goal of the learning process. However, in reality, the mathematics learning result of students in class XI MIPA SMAN 1 Lembah Gumanti are still low. One of the efforts that can be done to overcome these problems is by applying the Conceptual Understanding Procedures (CUPs) learning model. The purpose of this study was to determine whether the mathematics learning result of students who learned by applying the CUPs learning model were better than the mathematical learning result  of students whose learning by applying the direct learning model to students of class XI MIPA SMAN 1 Lembah Gumanti.Keywords – Conceptual Understanding Procedures (CUPs), Mathematics Learning Result